Discussing surgical innovation with patients: a qualitative study of surgeons' and governance representatives' views. Issue 11 (6th November 2020) - Zahra, Jesmond; Paramasivan, Sangeetha; Blencowe, Natalie S; Cousins, Sian; Avery, Kerry; Mathews, Johnny; Main, Barry G; McNair, Angus G K; Hinchliffe, Robert; Blazeby, Jane M; Elliott, Daisy
Abstract : Objectives: Little is known about how innovative surgical procedures are introduced and discussed with patients. This qualitative study aimed to explore perspectives on information provision and consent prior to innovative surgical procedures. Design: Qualitative study involving semi-structured interviews. Interviews were audio recorded, transcribed and analysed thematically. Participants: 42 interviews were conducted (26 surgeons and 16 governance representatives). Setting: Surgeons and governance representatives recruited from various surgical specialties and National Health Service (NHS) Trusts across England, UK. Results: Participants stated that if a procedure was innovative, patients should be provided with additional information extending beyond that given during routine surgical consultations. However, difficulty defining innovation had implications for whether patients were informed about novel components of surgery and how the procedure was introduced (ie, as part of a research study, trust approval or in routine clinical practice). Furthermore, data suggest surgeons found it difficult to establish what information is essential and how much detail is sufficient, and governance surrounding written and verbal information provision differed between NHS Trusts. Generally, surgeons believed patients held a view that 'new' was best and reported that managing these expectations could be difficult, particularly if patient views aligned with their own. Conclusions: This study highlights the challenges of information provision and obtaining informed consent in the context of innovative surgery, including establishing if and how a procedure is truly innovative, determining the key information to discuss with patients, ensuring information provision is objective and balanced, and managing patient expectations and preferences. This suggests that surgeons may require support and training to discuss novel procedures with patients. Further work should capture consultations where new procedures are discussed with patients and patients' views of these information exchanges.